Organic bases as additives for steam-assisted gravity drainage - Sean D. Brame (KeAi Communications Co., Ltd., 2019)
Abstract Steam-assisted gravity drainage (SAGD) is a mature technology for bitumen recovery from oil sands. However, it is an energy-intensive process that requires large amounts of steam to heat and mobilize bitumen. The purpose of this work is to develop ways to enhance SAGD performance through the use of organic base additives. The research is approached from three focus areas that supplement and guide each other: characterization tests, sand-pack floods, and computational simulation. A number of key mechanisms for enhancing oil recovery were identified, high-temperature additive characterization tests were developed, and promising alkalis were tested in porous media. Simulation was employed to history-match sand-pack flood production data, in order to demonstrate the effect of an additive on the oil–water relative permeability. Based on these results, it was concluded that oxygenated organic bases had the most potential for improving bitumen recovery through reducing the oil–water interfacial tension (IFT) by increasing the pH of the system. These organic bases favorably modify the interfacial energies between the immiscible oil–water phases and enable them to flow easily through the porous media during production. Sand-pack flood tests have successfully demonstrated a 10%–15% improvement in bitumen recovery, over baseline, in the presence of IFT-reducing additives. Simulation results further showed that an IFT reduction had a positive impact on SAGD performance. This work demonstrates the potential of organic bases to improve not only SAGD, but other steam injection processes. Furthermore, a number of experimental methods were developed, tried, and tested during the course of this work.